Sign up ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I have Maths test tomorrow and was just doing my revision when I came across these two questions. Would anyone please give me a nudge in the right direction?

$1)$ If $x$ is real and $$y=\frac{x^2+4x-17}{2(x-3)},$$ show that $|y-5|\geq2$

$2)$ If $a>0$, $b>0$, prove that $$\left(a+\frac1b\right)\left(2b+\frac1{2a}\right)\ge\frac92$$

share|cite|improve this question
For $a=b=1$ you have $\frac{a+1}{b}.\frac{2b+1}{2a}=3 < \frac92$, so the second one is probably not copied correctly. (Or the meaning was change by one of the edits.) – Martin Sleziak Jul 23 '12 at 10:05
BTW if you write that his question is from your preparation for the exam and revising, there's probably no need to tag it as homework. (Although I am aware that some users use this tag when they don't want to get full solutions, only hints/suggestions.) – Martin Sleziak Jul 23 '12 at 10:09
Is the second one supposed to be $(a+\frac1b)(2b+\frac1{2a})\ge\frac92$? This can be typeset as: $(a+\frac1b)(2b+\frac1{2a})\ge\frac92$. – Martin Sleziak Jul 23 '12 at 10:21
The second one is false as stated: for $a=b=1$ it says that $3\ge\frac92$. – Brian M. Scott Jul 23 '12 at 10:23
Thanks @martin , yeah, that was what my question was originally, but someone misunderstood my question and edited it in their way I guess. – Sophia Jul 23 '12 at 13:44

3 Answers 3

up vote 2 down vote accepted

For the first problem: Write it as $$ \begin{eqnarray} \left(y-5\right)^2-4&=&\left(\frac{x^2+4x-17}{2(x-3)}-5\right)^2-4\\ &=&\left(\frac{x^2+4x-17-10x+30}{2(x-3)}\right)^2-4\\ &=&\left(\frac{x^2-6x+13}{2(x-3)}\right)^2-4\\ &=&\frac{(x^2-6x+13)^2 - 16(x-3)^2}{4(x-3)^2}\\ &=&\frac{169-156 x+62 x^2-12 x^3+x^4 - 16x^2+96x-144}{4(x-3)^2}\\ &=&\frac{x^4 -12x^3+46x^2 -60x+25}{4(x-3)^2}\\ &=&\frac{(x^2 -6x+5)^2}{4(x-3)^2}\\ &=&\frac{(x-5)^2(x-1)^2}{4(x-3)^2}\ge 0 \end{eqnarray} $$ So only squares show up, hence it's positive.

share|cite|improve this answer
I've changed $-13$ to $+13$ in two spaces (probably a typo). BTW the same can be done with less intermediate steps as $(x^2-6x+13)^2-(4x-12)^2=(x^2-10x+25)(x^2-2x+1)=(x-5)^2(x-1)^2$; which is obtained using the formula $a^2-b^2=(a-b)(a+b)$ for $a=x^2-6x+13$ and $b=4x-12$. – Martin Sleziak Jul 23 '12 at 13:28
@MartinSleziak thanks – draks ... Jul 23 '12 at 13:29

Expression in (2) is $$ 2ab+\frac{1}{2ab}+\frac{5}{2} $$ Applying $AM \geq GM$ on the first two terms gives $$ 2ab+\frac{1}{2ab} \geq 2 $$ Substituting in the previous expression yields the given inequality.

share|cite|improve this answer

Only the first problem.

By long division you have $$y=\frac{x+7}2+\frac2{x-3}$$ and thus $$y-5=\frac{x-3}2+\frac2{x-3}.$$

So if you substitute $t=\frac{x-3}2$, it suffices to show $$\left|t+\frac1t\right|\ge2$$ for $t\ne 0$, which is the same as $$t+\frac1t\ge2$$ for $t>0$.

There are many methods how to show this last inequality.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.